Novel approach for treating challenging implant-borne maxillary dental rehabilitation cases of cleft lip and palate: a retrospective study - Björn Rahlf; Philippe Korn; Alexander-Nicolai Zeller; Simon Spalthoff; Philipp Jehn; Fritjof Lentge; Nils-Claudius Gellrich (SpringerOpen, 2022)
Abstract Purpose Dental restoration in cleft lip and palate (CLP) patients is demanding and often results in bone loss and dental implant failure. Furthermore, unfavorable conditions of hard and soft tissues as well as skeletal deformities aggravate surgical and dental treatment. Therefore, this study was designed to assess the feasibility of using a new type of patient-specific implant (IPS-preprosthetic®) in CLP patients. Methods Of the 63 patients who received a IPS-preprosthetic® implant in the Department of Oral and Maxillofacial Surgery at the Hannover Medical School, Germany, six patients were treated for a CLP deformity with significant soft and hard tissue impairment. Two patients were partially edentulous, whereas four patients were edentulous for the maxilla. All implants were inserted in a single-step outpatient surgery and were followed up for up to 40 months. Results Within the observation period, no implant failed and no screw loosening or change in stability of the implant to recipient site occurred (mean number of screws: 21). This study demonstrates, for the first time, the efficient use of a one-piece multivector screw primarily retained a stable patient-specific implant for implant-borne prosthodontic rehabilitation of CLP patients with deformities and challenging initial situations. Conclusions IPS-preprosthetic® implants offer a novel approach to implant dentistry treatment protocols, especially in difficult cases of unusual anatomy, even when previous conventional treatment fails.